Network Connectedness among Northeast Asian Financial Markets. Issue 13 (20th October 2020) - Lee, Hahn Shik; Lee, Woo Suk
ABSTRACT: Despite the increasing interest in the topic of international transmission of financial markets, the Northeast Asian region has received little attention concerning connectedness among financial markets. This article discusses network connectedness among financial markets in the Northeast Asian region. In particular, we investigate various aspects of international linkage across different asset-class (stock, bond, foreign exchange) markets in China, Japan, and Korea. The basic finding is that the connectedness among Northeast Asian countries seems rather weak, while the US markets are an important source of network effects on financial markets in this region. As for the dynamic aspects of connectedness, we observe time-varying patterns in connectedness measures, with a surge around the GFC. Also presented evidence that China has become more influential with the development of Chinese financial markets since the "new normal (Xinchangtai)" period.